2009
DOI: 10.1002/chem.200901998
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐by‐Layer Assembly of Polyelectrolyte and Nanoparticles, Monitored by Capillary Electrophoresis

Abstract: Layer-by-layer (LBL) assembly is a versatile nanofabrication technique, and investigation of its kinetics is essential for understanding the assembly mechanism and optimizing the assembly procedure. In this work, the LBL assembly of polyelectrolyte and nanoparticles were monitored in situ by capillary electrophoresis (CE) for the first time. The assembly of poly(diallyldimethylammonium chloride) (PDDA), and gold nanoparticles (AuNPs) on capillary walls causes surface-charge neutralization and resaturation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…It should be noted that in the column preparation process, the time for nega- tively charged AuNPs to stay in the capillary was 12 h, while that for positively charged AuNPs was only 30 min. Nevertheless, the surface coverage of the Type I column is still higher than that of Type III even though recent research showed that the adsorption of AuNPs onto a PEM coated capillary wall is a slow process that needs at least 1 h to reach saturation of the AuNPs [36,46]. Thus, this experimental result also indicates that the adsorption rate of DMAP capped AuNPs onto the PEM coated capillary wall is very fast.…”
Section: Resultsmentioning
confidence: 43%
“…It should be noted that in the column preparation process, the time for nega- tively charged AuNPs to stay in the capillary was 12 h, while that for positively charged AuNPs was only 30 min. Nevertheless, the surface coverage of the Type I column is still higher than that of Type III even though recent research showed that the adsorption of AuNPs onto a PEM coated capillary wall is a slow process that needs at least 1 h to reach saturation of the AuNPs [36,46]. Thus, this experimental result also indicates that the adsorption rate of DMAP capped AuNPs onto the PEM coated capillary wall is very fast.…”
Section: Resultsmentioning
confidence: 43%
“…CZE 138, 139, MEKC 139, or CE using a polymer additive as sieving medium 140. Likewise, CE in different modes can be utilized to verify the conjugation of quantum dots with proteins 141, ligand molecules 142, and antibodies 143; to separate nanoparticles of TiO 2 and Al 2 O 3 from a mixed suspension 144 or gold nanoparticles (Au‐NP) at trace concentrations following reversed electrode‐polarity stacking 145, 146; to characterize differently functionalized bifunctional Fe 2 O 3 –SiO 2 nanoparticles 147 or the ligand‐protected Au‐NP 148; to monitor the assembly of a polyelectrolyte and Au‐NP on capillary walls 149 etc. Perhaps the most interesting example over the reviewed period concerns the CE‐ICP‐MS assaying of free and albumin‐bound Au‐NP in human urine 150.…”
Section: Speciation Analysismentioning
confidence: 99%
“…This deposition technique results in a multilayer complex that is predominantly stabilized by strong electrostatic interactions. [13] Many studies have been performed to better understand the adsorption and formation of PEM systems in a capillary [13][14][15][16][17][18][19][20][21] and the specific effects of various system variables, including: (1) the type of polyelectrolyte, [22][23][24][25] (2) ionic strength, [18,24,[26][27][28] (3) dynamics of counterions, [29,30] and (4) short range interactions, [24,31] on the properties of useful PEM systems. These reports have established a wide range of useful conditions for developing PEM systems with widely varied properties.…”
Section: Introductionmentioning
confidence: 99%